Clinical profile and outcome of cardiac involvement in MELAS syndrome. (1st February 2019) - Brambilla, Alice; Favilli, Silvia; Olivotto, Iacopo; Calabri, Giovanni Battista; Porcedda, Giulio; De Simone, Luciano; Procopio, Elena; Pasquini, Elisabetta; Donati, Maria Alice
Abstract: Background: Mitochondrial myopathy, encephalopathy, lactic acidosis and stroke-like (MELAS) syndrome is a rare condition with heterogeneous clinical presentation. Cardiac involvement commonly develops during adulthood, comprising both structural and conduction/arrhythmic abnormalities; early paediatric onset has rarely been reported. We describe the clinical profile, outcome and clinical implication of MELAS-associated cardiomyopathy at a tertiary referral centre. Methods: From 2000 to 2016 we enrolled 21 patients affected by genetically-proven MELAS. Patients were followed-up at least annually over a mean of 8.5 years. Results: All patients carried the MT-TL1 3243A>G mutation. Cardiac involvement was documented in 8 (38%) patients (three <18 years; five ≥18 years), including 6 (75%) with hypertrophic cardiomyopathy, 1 (12.5%) with dilated cardiomyopathy, and 1 (12.5%) with persistent pulmonary hypertension. During follow-up, 3 patients died, all with cardiac onset <18 years. The cause of death, however, was non-cardiac (infections, respiratory failure, stroke). Neither events nor cardiac progression were recorded among patients with onset ≥18 years. Adult cardiologists were responsible for 5/8 of referrals, even in patients with long-standing extra-cardiac involvement. Conclusions: Cardiac involvement was found in over 1/3 of patients with MELAS syndrome, and exhibited a bimodal age-related distribution with distinct final outcomes. Paediatric-onset cardiomyopathy represented a hallmark of systemic disease severity, without being the main determinant of outcome. Conversely, adult-onset cardiomyopathy appeared to represent a mild and non-progressive mid-term manifestation. Adult cardiologists played an important role in the diagnostic process, triggering suspicion of MELAS in most of patients diagnosis >18 years. Highlights: Cardiac involvement (CI) in MELAS exhibited a bimodal age-related distribution. A more aggressive clinical course should be expected in case of paediatric-onset CI. Adult-onset heart involvement seemed stable over time, at least in the mid-term. CI is a useful red flag for diagnosis when associated with extra-cardiac features. Adult cardiologists may play a central role in the diagnostic pathway.